Effect of Educational Intervention on Knowledge, Practice, and Attitude of General Practitioners Regarding Lesions of the Oral Cavity - Mehrnaz Dezfouli; Fatemeh Rashidi meybodo; elnaz Ahrami; Hajar shekarchizadeh (Mashhad University of Medical Sciences, 2020)
Introduction: Oral hygiene is one of the main components of public health and people's quality of life which by early diagnosis of oral diseases, their prognosis and treatment will be accelerated. Therefore, the present study aimed to intervene and assess the knowledge, performance, and attitude among general practitionersregarding the oral cavity lesions. Materials and Methods: The current quasi-experimental research was performed on 75 general practitioners participating at re-training courses at the Medical Education Development Center of Isfahan University of Medical Sciences, Isfahan, Iran. The data collection tool was a structured questionnaire consisting of two sections. The first section contained demographic information and the second included knowledge, performance, and attitude regarding oral lesions. The obtained data were analyzed in SPSS software (version 20) using the t-test and Pearson's correlation coefficient. Results: The results of the present study indicated that the mean score of academic and clinical knowledge, attitude, and practice of general practitionersshowed a significant difference among the three post-intervention periods (P≤0.001). According to Pearson's correlation coefficient test, the mean score of attitude and practice showed a statistically significant relationship with age (P=0.001, P=0.03) and duration of medical practice (P=0.002, P=0.02); however, there was no statistically significant relationship with the number of patient visits per day (P=0.61, P=0.29). Furthermore, no significant relationship was observed between academic and clinical knowledge with age (P=0.92, P=0.59), duration of treatment (P=0.93, P=0.92), and the number of patient visits per day (P=0.77, P=0.85). Conclusion: Considering the positive impact of the intervention in the current research, one of the effective factors in the prevention of oral cavity lesions is the promotion of general practitioners and health-care personnel's knowledge through in-service and integrated training programs.